Event‐triggered distributed consensus control of nonlinear multi‐agent systems with unknown Bouc–Wen hysteresis input and DoS attacks - Guo, Shiyu; Xu, Ning; Niu, Ben; Zhao, Xudong; Ahmad, Adil M. (International journal of adaptive control and signal processing, 2024)
In this paper, the event‐triggered distributed consensus tracking control problem for a class of multi‐agent systems (MASs) is studied, where denial‐of‐service (DoS) attacks and Bouc‐Wen hysteresis inputs are considered in the communication channel and the actuator, respectively. First, when communication networks are subject to malicious DoS attacks, the connection weights of the communication topology graphs are affected. To address this problem, this paper establishes topological models of the communication network using a switching topology method, and gives connection recovery strategies for the communication network. Second, in order to save communication resources, a distributed control protocol based on an event‐triggered mechanism and locally deployed estimator is designed for DoS signals occurring in the communication network of states and control inputs. In addition, the effect of unknown Bouc–Wen hysteresis input is eliminated using the Nussbaum‐type function. Then, based on Lyapunov stability theory, the boundedness of all signals in the closed‐loop system is verified, and the objective of consensus control is achieved. Finally, the effectiveness of the proposed control scheme is demonstrated by numerical and practical simulation examples.